Uma Aboradgem multivariada da evolução da gestão da qualidade total nas indústrias de transformação de médio e grande porte do Estado do Ceará - Rodriguês, Jarbas Silva (2010)
This work is mainly aimed at conducting a study to investigate the main aspects of the development of processing industries, medium and large companies, the state of Ceará, with regard to implementation of the practices of Total Quality Management. We used the technique of Factor Analysis and Cluster, for the identification and characterization of these developments in a comparative study conducted by the Alexander (1999). The methodology used in research for data collection was to quantitative research. The data collection instrument consisted of a questionnaire with a Likert scale with five ordered response categories. 86 companies were survey ed in 2009, and compared with results obtained from 69 companies surveyed by Alexander (1999) in 1998. Overall, there was a change in characterization and prioritization of the practices of TQM, from 1998 to 2009. It is observed that for 1998, the practices of TQM presented three basic priorities of importance, in view of the companies: "Commitment of top management", "Training" and "Opinion of the employees to improve quality." This pattern was changed in 2009 when the three most important were: "Metrology," "Meet the staff" and "Metrology." Such changes impact, either directly, implementing these quality management practices within companies.